Analisa Teknik Penerjemahan serta Pergeseran Bentuk dan Makna pada Lirik Lagu Shout to The Lord - Mercy Marcellina; Febrian Febrian (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Translating literatures and scientific texts are two different translation processes of text and form. While translating a song, the translator should maintain the meaning, and produce translated lyric that can be sung with the same nuance and notation as the source language. In practice, the use of techniques and shifts is a common challenge found in translating song. This study aims to analyze translation techniques, shifts, and factors underlying shifts in form and meaning. This study is type of qualitative descriptive research. The data source used is translation of song titled Shout to the Lord. This study found that a song lyric can’t be translated literally, several datas were translated using more than one technique and shifts. The results of the analysis of translation techniques showed that 40% datas translated using transposition technique, 13.33% datas used reduction technique, 6.67% other datas used amplification technique, 40% datas used combination technique. Meanwhile, the results of the analysis of the types of shifts in 15 datas showed that 6.67 data experienced level shift, 6.67% datas experienced structural shifts, 26.66% datas experienced unit shifts, 13,33% datas experienced specific to generic meaning shifts and vice versa, 46,67% datas experienced more than 1 type of shift